COVID - 19 AND ITS IMPACT ON MSMES IN INDIA - Shashikala, (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Micro, Small and Medium Enterprises (MSME) forms the backbone of the Indian economy and is one of the most crucial segments that let the economy grow by leap and bounds. The micro, small and medium enterprises as a whole form a major chunk of manufacturing in India and play an important role in providing large scale employment and also in the country’s exports. Recent annual reports on MSMEs indicate that the sector contributes around 30% of India’s GDP and based on conservative estimates, employs around 50% of industrial workers. Over 97% of MSMEs can be classified as micro firms (with an investment in plant and machinery less than Rs. 25 lakhs) and 94% are unregistered with the government. Many of the micro enterprises are small, household run businesses. Now the world is battling with modern horrors like the Covid-19, which has left the entire world befuddled and in the lurch as to hop one virus has brought the entire world to a standstill. The Covid-19 pandemic has left its impact on all sectors of the economy, but now here is the hurt as much as the MSMEs of India. MSMEs have been the worst casualty of Covid-19 induced lockdown.